Congenital band causing small bowel obstruction in a newborn - Mariam Marzouki; Awatef Charieg; Intissar Chibani; Meriem Oumaya; Yosra Ben Ahmed; Tarek Boukesra; Faouzi Nouira; Said Jlidi (Elsevier, 2021)
Introduction: Intestinal atresia refers to a complete obstruction of the bowel lumen. Anomalous congenital bands are rarely found as causes of intestinal obstruction in children. Most congenital bands occur in the small intestine. This report presents 1-day-old newborn girl with intestinal atresia due to a congenital band. Observation: We report a case of a full-term female newborn who presented with symptoms and signs of intestinal obstruction. She was in good condition with bilious residue in the gastric tube, abdominal distension and compressible wall. Anus was in normal position. Introduction of a rectal tube found no obstacle and brought no meconium. X-ray examinations have shown digestive obstruction. Surgical intervention was performed. There was a congenital band identified between a dilated ileal loop and the mesentery causing compression and ileal atresia. Surgical procedures consisted of section of congenital band and resection of dilated aperistaltic small bowel, cecum and appendix. We then proceeded to end-to-end ileocolic anastomosis. The patient recovered without complications. Conclusion: Congenital bands are a rare cause of intestinal atresia in neonate. This entity is very uncommon and difficult to identify preoperatively. Surgery is necessary and diagnosis of intestinal atresia due to congenital band is then confirmed.